Effect of Mn Doped Ni−Co Mixed Oxide Catalysts on Urea Oxidation. Issue 13 (5th May 2022) - Santhosh, Shilpa; Teller, Hanan; Schechter, Alex; Kalarikkal, Nandakumar
Abstract: Urea as an energy generation and storage fuel has attracted increased attention for its stability, non‐toxicity, and availability. Urea possesses 10.1 wt.% of hydrogen. Nevertheless, its electrochemical oxidation is generally sluggish and inefficient. Ni‐based catalysts which showed efficient activity towards urea electrooxidation in the alkaline medium were studied for Direct Urea Fuel Cell (DUFC) anodes. In the present study, we investigated urea oxidation on a novel three‐dimensional mixed oxide catalyst, NiCo2 O4 . Mn‐doped NiCo2 O4 catalyst exhibited urea oxidation activity of 45.88 mA cm −2 (at 1.30 V vs SHE), fifteen times higher than NiO and Co3 O4 and twice that of bare NiCo2 O4 spinel. Chronoamperometry curves of the Mn‐doped NiCo2 O4 catalyst demonstrated stable urea oxidation for over 3 hours. The significantly higher mass activity of Mn‐doped NiCo2 O4 catalyst is attributed to the least nano‐crystallite size, better dispersion of Ni nuclei onto the spinel crystal matrix, enhanced Ni electrochemical active surface area, and lower bandgap. Abstract : Dispersion : Urea is considered as a potential, non‐toxic, stable and abundant generation and storage fuel. Mn‐doped NiCo2 O4 mixed oxide catalyst showed substantially higher urea oxidation activity than the undoped ternary and binary catalysts. This significantly higher activity is attributed to the least nano‐crystallite size, better dispersion of Ni nuclei onto the spinel crystal matrix, and lower bandgap.